2021
DOI: 10.1177/09610006211016509
|View full text |Cite
|
Sign up to set email alerts
|

Academicians’ awareness, attitude, and use of open access during the COVID-19 pandemic

Abstract: The aim of this research is to reveal academics’ awareness, attitude, and use of open access. In line with the research purpose, the survey research design is adopted. This research consists 151 academics from 12 basic research areas; eight of them being Professor Dr, 17 being Associate Professor Dr, 49 being Doctor Lecturer, and 77 being Research Assistant or Lecturer. A questionnaire consisting of 19 open access and five demographic information questions was used for the data collection tool. The research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…The results reported that a majority of the students use OA resources for academic purposes, which signify positive attitude of the students toward OA platforms. These results are consistent with the findings of some previous studies (Dulle and Minishi-Majanja, 2009; Prince and Saravanan, 2015; Sheikh, 2019; Turgut et al. , 2021).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results reported that a majority of the students use OA resources for academic purposes, which signify positive attitude of the students toward OA platforms. These results are consistent with the findings of some previous studies (Dulle and Minishi-Majanja, 2009; Prince and Saravanan, 2015; Sheikh, 2019; Turgut et al. , 2021).…”
Section: Discussionsupporting
confidence: 94%
“…The results reported that a majority of the students use OA resources for academic purposes, which signify positive attitude of the students toward OA platforms. These results are consistent with the findings of some previous studies (Dulle and Minishi-Majanja, 2009;Prince and Saravanan, 2015;Sheikh, 2019;Turgut et al, 2021). Zhang and Li (2015) reported that a majority of the respondents were unaware of the process of depositing articles in institutional repositories, which was a major hurdle for student not to self-archive.…”
Section: Discussionsupporting
confidence: 91%
“…There are also some surprising results of surveys, such as that researchers in the arts and human sciences would be more positive towards OS (Ostaszewski, 2014). Overall, awareness of OA increased during the pandemic (Turgut et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Awareness of OA among researchers has increased over the years (Rodriguez, 2014; Turgut et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although researchers' engagement with OA has increased substantially in the previous five to ten years, their perceptions of OA have remained consistent because they perceive OA publication to be of lower quality, less prestigious, and less credible (O'Hanlon et al. , 2020; Rodriguez, 2014; Turgut et al. , 2021; Yang et al.…”
Section: Literature Reviewmentioning
confidence: 99%